PEMBELAJARAN BERFOKUS PADA PELANGGAN (Studi dari FKIP UR dan Fakultas Tarbiyah UIN Pekanbaru) - Rr Sri Kartikowati (Program Studi Pendidikan Ekonomi Universitas Riau, 2016)
Is 'customer is the king' could be applied in the context of education? Is the teaching in a University should take place by highly considering expectations of the customers (students)? This study answered such curiosity. The study aimed to generate a particular map (mapping) or portrait of lecture highlighted by the concept of customer focus. This study was conducted at two universities, the University of Riau (UR) and the State Islamic University (UIN), located in Pekanbaru. Data is collected through a simple questionnaire designed to obtain information about two things: the expectations and the reality received by customer (students), focused on 10 aspects of learning. The greater the difference between the two scores that indicate the quality gap in the implementation of learning. The data, then, is analyzed descriptively for describe the level of conformance in the concept of 'customer focus'. The study found three bigest quality gap (from 10 aspects measured) on learnig highligted by customer focus concept, which is similar, at the two universities studied, are: (1) The application of student centered approach; (2) Transparency of assessment; and (3) Discussion on mid test.